Tirzepatide for type 2 diabetes - Sarah L Anderson; Joel C Marrs (BioExcel Publishing Ltd, 2023)
One in ten adults worldwide is living with diabetes, with 95% having type 2 diabetes (T2D). Sustained glycaemic control in people with T2D is difficult to achieve despite recent advances in T2D management with the advent of glucagon-like peptide 1 receptor agonists (GLP1RA) and sodium-glucose cotransporter 2 inhibitors (SGLT2i). Tirzepatide represents a first-in-class agent as a dual glucose-dependent insulinotropic polypeptide (GIP)/GLP1RA to be approved in the USA and Europe for the treatment of T2D. This narrative review intends to list and discuss the glycaemic efficacy, key safety and weight loss outcomes related to the treatment of T2D with tirzepatide. Tirzepatide has been evaluated in five published clinical trials (n=6278) within the SURPASS clinical trial programme, with a focus on glycaemic control and weight loss. These trials have demonstrated significant improvements in glycosylated haemoglobin (-1.24% to -2.11% versus placebo and -0.6% to -1.14% versus active comparator) and weight (up to 15.5 kg versus placebo or active comparator) in patients with T2D. Notably, tirzepatide exhibited superior glycaemic control and weight loss when compared directly with a GLP1RA. Adverse events with the use of tirzepatide are similar to other approved GLP1RA and are predominantly gastrointestinal (nausea, vomiting). The tirzepatide cardiovascular outcomes trial (SURPASS-CVOT) is in progress and is expected to be completed in the fall of 2024. Tirzepatide represents an attractive new option and first-in-class agent for the treatment of T2D in people unable to achieve their glycaemic or weight management goals.